TRAININGS AS A KIND OF INFORMAL EDUCATION AND THEIR EFFICIENCY FOR EDUCATIONAL PROCESS: EXPERIENCE AND PROSPECTS - Blyznyuk, Tetyana (Mountain School of Ukrainian Carpaty, 2022)
The article shows pedagogical potential of trainings as an innovative way of obtaining informal education and self-development of a specialist of the New Ukrainian School. The interpretation of the notion “informal education” by the scientific community is considered, the characteristics of informal education are given, the possible institutions of its receipt are listed. The content of various forms of informal education in the direction of improving the digital competence of teachers is determined. The best experience of organizing and conducting trainings on professional development of scientific and pedagogical workers on the basis of the Center of Innovative Educational Technologies "PNU EcoSystem" of Precarpathian National University is widely presented. It is proved that the practice of such work is effective in the context of the New Ukrainian School, as it is based on the best experience of trainers gained during numerous study visits to leading universities in the world, claiming the best innovative developments for improvement of learning process. The training of primary school teachers has evidenced the effectiveness of such trainings, as they not only promote creative interaction of participants, but also develop the ability to use practical skills and interesting educational content; encourage the enhancement of general cultural and professional development of learners; meet socio-communicative and intellectual needs; stimulate professional self-perfection. The experience of organizing training shows that participants who are familiar only with the basic use of digital tools, tend to apply them more meaningfully in their teaching practice. The research proves, a competent teacher is able not only to use but also to create innovative developments, taking into account their maximum potential in the educational context.